2020
DOI: 10.1002/adfm.202008813
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Smooth Graphene‐Based Hybrid Template for the Epitaxial Growth of Organic Semiconductor Crystals

Abstract: Atomically thin 2D materials are good templates to grow organic semiconductor thin films with desirable features. However, the 2D materials typically exhibit surface roughness and spatial charge inhomogeneity due to nonuniform doping, which can affect the uniform assembly of organic thin films on the 2D materials. A hybrid template is presented for preparation of highly crystalline small‐molecule organic semiconductor thin film that is fabricated by transferring graphene onto a highly ordered self‐assembled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 42 publications
0
37
1
Order By: Relevance
“…This extremely low value of 1.75 nW cm −2 is the lowest detectable power among reported NIR graphene/organic phototransistors (Table 1). [20][21][22][23][24][25][26] In order to more visually demonstrate device photoresponse, we measured and calculated wavelength-dependent R by formula: R = I ph /P, [47] where I ph is the photocurrent and P is incident light intensity, and relevant curves are displayed in Figure 2b. It can be seen that a broad region photoresponse covering 488-1064 nm with high R more than 10 5 A W −1 corresponds to overlapping of each component absorption in T-BHJ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extremely low value of 1.75 nW cm −2 is the lowest detectable power among reported NIR graphene/organic phototransistors (Table 1). [20][21][22][23][24][25][26] In order to more visually demonstrate device photoresponse, we measured and calculated wavelength-dependent R by formula: R = I ph /P, [47] where I ph is the photocurrent and P is incident light intensity, and relevant curves are displayed in Figure 2b. It can be seen that a broad region photoresponse covering 488-1064 nm with high R more than 10 5 A W −1 corresponds to overlapping of each component absorption in T-BHJ.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] However, their performance in the NIR region is facing severe challenges. [20][21][22][23][24][25][26] Generally, the structures of reported graphene/organic phototransistors are only simply preparing single organic materials (SOMs) or planar heterojunctions (PHJs) as photosensitive layer (PSL) on graphene and have no extraction layer. In such structure, phototransistors suffer from either short-wavelength absorption limitation leading to no NIR region response or low dissociation efficiency and poor charge extraction rate resulting in restricted NIR-photocurrents.…”
Section: Jonesmentioning
confidence: 99%
“…A group of PHJ type-II D-A systems are brought into the 2D photoconductive structure, including PTCDA/pentacene, [39] PTCDA/C 8 -BTBT, [143] C 60 /pentacene, [61,141] C 60 /ZnPc. [144] Chen et al used sequential vdW epitaxy to demonstrate the high quality muti-layer graphene/PTCDA/pentacene phototransistor suggests that few nanometers of optimized interlayer ensure Figure 6.…”
Section: Schottky Junction Integrated With Bhj and Phj In Planar Stru...mentioning
confidence: 99%
“…[145] And on this basis, Nguyen et al optimized the substrate and realized uniform assembly of C 60 /pentacene onto graphene with increase in effective length of exciton (Figure 7e,f). [61] By variation of interlayer in similar configuration, He et al revealed the parts of the internal transport phenomenon by competition mechanism, giving an operation speed of 10 KHz. [144] On the contrary, the symmetric electrode on Poly-TPD:PCBM with both BHJ and WS 2 for light-absorbing.…”
Section: Schottky Junction Integrated With Bhj and Phj In Planar Stru...mentioning
confidence: 99%
See 1 more Smart Citation